Qualitative and Quantitative Wall Enhancement Analyses in Unruptured Aneurysms Are Associated With an Increased Risk of Aneurysm Instability - Zhang, Yi; Fu, Qichang; Wang, Yuting; Cheng, Jingliang; Ren, Cuiping; Guan, Sheng; Zhu, Chengcheng (Frontiers in Neuroscience, 2020)
Objective: Intracranial aneurysm wall enhancement (AWE) is independently associated with unstable aneurysms. However, a quantitative analysis of wall enhancement is lacking. This study aimed to investigate the relationship between qualitative and quantitative wall enhancement indices (WEIs), traditional risk factors for aneurysms, and clinical ELAPSS/PHASES scores in a large cohort of intracranial saccular aneurysms. Methods: In this cross-sectional study, a total of 174 patients (mean age 60.4±9.5 years; 53% women) with 248 asymptomatic unruptured intracranial aneurysms underwent pre- and post-contrast black-blood magnetic resonance imaging (MRI). The extent of AWE was defined as non-AWE (pattern 0), focal AWE (pattern 1), or circumferential AWE (pattern 2). WEI was calculated using wall signal intensities on pre- and post-contrast images. Predicted 3- and 5-year growth risk and 5-year rupture risk were obtained from ELAPSS and PHASES scores, respectively. Uni- and multivariate analyses were conducted to explore the relationship between AWE characteristics, risk-related factors, and aneurysm instability. Results: Aneurysm size (odds ratio [OR], 1.3; 95% confidence interval [CI], 1.2–1.4; P < 0.001), non-internal carotid artery/middle cerebral artery location (OR, 1.9; 95% CI, 1.0–3.6; P = 0.045), and irregular shape (OR, 2.4; 95% CI, 1.2–4.5; P = 0.009) were independently associated with AWE. For aneurysms with AWE, the estimated 3- and 5-year growth risk (25.3 ± 13.0% and 38.0 ± 17.4%) and the 5-year rupture risk (3.9±5.2%) were 1.9–3.3-fold higher than those for aneurysms without AWE (12.8 ± 9.1%, 20.3 ± 13.0%, and 1.2 ±1.6%, respectively; all P < 0.001). Larger areas and higher WEIs of enhancement positively correlated with aneurysm size (r = 0.43 and 0.38, respectively), 3- and 5-year growth risk, and 5-year rupture risk (r = 0.49 and 0.40, r = 0.49 and 0.40, r = 0.36 and 0.24, respectively; all P < 0.001). In sum, a larger aneurysm size, non-internal carotid artery/middle cerebral artery location, and irregular shape were independently associated with AWE. Larger areas and higher WEIs were associated with an increased risk of aneurysm growth and rupture. These findings suggest that quantitative AWE metrics should be considered in future large-scale longitudinal studies to evaluate their value in aneurysm risk management.